Kesiapan Masyarakat Dalam Penanganan Pre Hospital Covid-19 Di Surabaya : Studi Kualitatif - Nur Mukarromah; Siswanto Agung Wijaya; Septian Galuh Winata; Erfan Rofiqi; Diah Priyantini (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Pre-hospital conditions in handling COVID-19 were part of the mortality rate before the patient was taken to the hospital. The purpose of this study was to determine the community's readiness in handling pre hospital covid-19 in Surabaya. Methods: This article design was descriptive using a qualitative research approach. Results: The results of the study show that there were four themes are related how the condition of the community's readiness in handling pre-hospital Covid-19 was factors of knowledge, technology and infrastructure, politics and power, socialConclusion: The readiness of the community in handling pre-hospital Covid-19 can be described using the transcultural care model by assessing factors of knowledge, technology and infrastructure, politics and power, social.